2002
DOI: 10.1094/phyto.2002.92.7.743
|View full text |Cite
|
Sign up to set email alerts
|

Use of Green Fluorescent Protein-Transgenic Strains to Study Pathogenic and Nonpathogenic Lifestyles inColletotrichum acutatum

Abstract: Colletotrichum acutatum, which causes anthracnose disease on strawberry, can also persist on several other plant species without causing disease symptoms. The genetic and molecular bases that determine pathogenic and nonpathogenic lifestyles in C. acutatum are unclear. We developed a transformation system for C. acutatum by electroporation of germinating conidia, and transgenic isolates that express the green fluorescent protein (GFP) were produced. Details of the pathogenic and nonpathogenic lifestyles of C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 30 publications
6
50
0
1
Order By: Relevance
“…The presence of subcuticular, intramural, and intra-or inter-cellular hyphae in leaf tissues disagrees with results of Leandro et al (2001), who did not detect host penetration of strawberry leaves by C. acutatum. However, our observations agree with those of Horowitz et al (2002), who detected the fungus inside strawberry leaves.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The presence of subcuticular, intramural, and intra-or inter-cellular hyphae in leaf tissues disagrees with results of Leandro et al (2001), who did not detect host penetration of strawberry leaves by C. acutatum. However, our observations agree with those of Horowitz et al (2002), who detected the fungus inside strawberry leaves.…”
Section: Discussionsupporting
confidence: 93%
“…Microcyclic conidiation or conidiogenesis was observed on both adaxial and abaxial surfaces of attached strawberry leaves. This process has already been described in C. capsici on cowpea leaves (Latunde-Dada et al 1999) and in C. acutatum on detached (Leandro et al 2001) and attached (Horowitz et al (2002) strawberry leaves, which may have implications on disease epidemics. However, on strawberry petioles, conidiogenic structures were not found.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Talhinhas et al, (2005) with molecular and phenotypic assays reported that the occurrence of C. acutatum in Portuguese olive orchards was higher (>97%) than C. gloeosporioides (<3%). The C. acutatum J. H. Simmonds is one of the most pathogenic species, which causes anthracnose and blight in agriculturally important hosts including many dicotyledonous plants such as strawberry, apple, citrus, and stone fruits (Horowitz et al, 2002;Peres et al, 2005).…”
Section: Introductionmentioning
confidence: 99%